Let's explore eggs! - Colella, Jill (2021)
"Eggs are a delicious, nutritious, and versatile! Introduce young readers to the chickens and their farmers, learn to cook a simple egg and toast dish, then make plant pots from the shells"--
Includes bibliographical references and index.
Ages 4-8
Grades K-1
Keywords: Cooking (Eggs); Eggs as food; Cookbooks